Computer aided learning package for electronic keyboard / Goh Yeh Hwang - Goh, Yeh Hwang (2003)
It is a compulsory to fulfill the WXE 3181 anda WXES 3182, in order to complete the entire course, Bachelor of Science computer, University of Malaya. The objective of internship training is to expose students to the real situation for process of operations, development and management in order to produce a group of high quality students. I was selected the project title: Computer Aided Learning Package for Electronic Keyboard while the entire courseware teaches fundamental skills to play electronic keyboard, including the elementary sight reading and music theories. This courseware was designed using Modern Object Oriented approach, Unified Modeling Language and platform independents solution Java technology. The key feature of this courseware are user friendliness, easy to understand, platform independent. CD-ROM based lessons, add-in tutorial and games with minimal installation requirement.